A propósito da investigação sobre cerâmica islâmica em Portugal - Isabel Inácio; Constança dos Santos; Catarina Coelho; Marco Liberato; Ana Sofia Gomes; Jacinta Bugalhão; Helena Catarino; Sandra Cavaco; Jaquelina Covaneiro; Isabel Cristina Fernandes; Susana Gómez; Maria José Gonçalves (Medievalista)
The first references on Islamic pottery in Portugal go back to the end of the nineteenth century. The modest evolution of the research until the 1980s was replaced by the development of the studies on this subject, pressed forward by the fundamental projects of Mértola and Silves. In the 1990s, this development was intensified and, in the last decade, the number, diversity and geographical dispersion of studies and projects was remarkable, particularly those originated from urban archaeology. The CIGA project (Cerâmica Islâmica do Ġarb al-Andalus), started in 2008, is part of this dynamics, promoting the systematization, the discussion and the diffusion of all the information and presenting here a composite paper about the studies on Islamic ceramics in Portugal, its main tendencies, problems, virtues and future perspectives.